Altered Light Conditions Contribute to Abnormalities in Emotion and Cognition Through HINT1 Dysfunction in C57BL/6 Mice - Zhou, Yuan; Zhang, Hao-kang; Liu, Fei; Lei, Gang; Liu, Peng; Jiao, Tong; Dang, Yong-hui (Frontiers in Behavioral Neuroscience, 2018)
In recent years, the environmental impact of artificial light at night has been a rapidly growing global problem, affecting 99% of the population in the US and Europe, and 62% of the world population. The present study utilized a mouse model exposed to long-term artificial light and light deprivation to explore the impact of these conditions on emotion and cognition. Based on the potential links between histidine triad nucleotide binding protein 1 (HINT1) and mood disorders, we also examined the expression of HINT1 and related apoptosis factors in the suprachiasmatic nucleus (SCN), prefrontal cortex (PFC), nucleus accumbens (NAc), and hippocampus (Hip). Mice exposed to constant light exhibited depressive- and anxiety-like behaviors, as well as impaired spatial memory, as demonstrated by an increased immobility time in the tail suspension and forced swimming tests, less entries and time spent in the open arms of elevated plus-maze, and less platform site crossings and time spent in the target quadrant in the Morris water maze. The effects of constant darkness (CD) partially coincided with long-term illumination, except that mice in the CD group failed to show anxiety-like behaviors. Furthermore, HINT1 was upregulated in four encephalic regions, indicating that HINT1 may be involved in mood disorders and cognitive impairments due to altered light exposure. The apoptosis-related proteins, BAX and BCL-2, showed the opposite expression pattern, reflecting an activated apoptotic pathway. These findings suggest that exposure to constant light and/or darkness can induce significant changes in affective and cognitive responses, possibly through HINT1-induced activation of apoptotic pathways.